CTLA-4 and PD-1 Pathway Blockade: Combinations in the Clinic - Callahan, Margaret K.; Postow, Michael A.; Wolchok, Jedd D. (Frontiers in Oncology, 2015)
Checkpoint blocking antibodies targeting regulatory molecules on T cells such as CTLA-4 and PD-1 have reinvigorated the field of cancer immunotherapy. These agents have demonstrated clinical activity across a variety of tumor types. Now that safety and clinical activity has been demonstrated in the monotherapy setting, the field is moving in the direction of testing novel combinations.